Comment on "general Non-Markovian Dynamics of Open Quantum Systems" - Mccutcheon, Dara Patrick Stephen (2015)
The existence of a on-Markovian dissipationless" regime, characterized by long lived oscillations, was reported in [1] for a class of quantum open systems. It is claimed this could happen in the strong coupling regime, a surprising result which has attracted attention. We show that this regime exists if and only if the total Hamiltonian is unbounded from below, casting serious doubts on the usefulness of this result.